(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to examine the effectiveness of the Problem-Based Learning (PBL) strategy on students’ understanding of the concept of travelling violation in basketball. The proposed hypothesis is that the PBL strategy is more effective than conventional teaching methods in improving students’ conceptual understanding of the material. The research employed a quantitative approach using a quasi-experimental design of the non-equivalent control group type. The sample consisted of 30 eighth-grade students from a public junior high school in Trenggalek Regency, divided into an experimental group and a control group using purposive sampling techniques. The research instrument was a multiple-choice test developed based on indicators of conceptual understanding. Data were analyzed using an independent t-test with the assistance of SPSS version 21. The results showed a significant difference between the posttest scores of the two groups, with a significance value (Sig. 2-tailed) of 0.001 < 0.05. The experimental group achieved a higher mean score (84.27) compared to the control group (72.13). These findings indicate that the PBL strategy is effective in enhancing students’ understanding of the travelling concept by encouraging active thinking and discussion. The implications of this research highlight the importance of implementing PBL strategies in physical education learning, especially in materials that require conceptual understanding of game rules. Further studies are recommended to be conducted over a longer period and on other physical education topics. Additional materials in this study include 9 references and 2 data analysis tables.